Faktor Berkah dalam Pola Konsumsi dan Tingkat Kepuasan untuk Pemenuhan Kebutuhan - Imam Barokah (AL-Muqayyad, 2020)
A person can make a living with their needs. Needs are inseparable from humans. Every human being demands to be able to meet his needs. In its development, the needs always change according to an individual. Will increase and decrease according to the existing factors. Needs are more than desires that must be fulfilled before desires. Even though the two are different, some people consider them the same. People who are good at sorting will know the difference between desire and needs. This study discussed individual satisfaction with their needs, individual efforts to meet their needs, as well as identifying individual needs in a place. The data was collected through direct observation and interviews. This research was important for the community to know their needs. So that it can be seen directly the responsibility of the community regarding needs. From the data, it can be seen that there were different needs of the community and they also attach the important factor of the blessing.